The influence of age, savings balance, and salary on the amount of customer deposit savings at bank XYZ - Wiguna, Nathania; Ardi, Ardi; Berlianto, Margaretha Pink (Enrichment : Journal of Management, 2024)
The increasing number of money supply in society from year to year, in 2020 it has increased by 12.4%. in 2021 it increased by 13.9%, and in 2022 it increased by 8.3%. Increasing money supply in society can trigger effects such as uncontrolled inflation and decrease interest rate especially for deposit savings. This study will find out which variables have a positive influence in making people want to save their money in Bank in long term savings which is time deposit. Data utilized in this research consist of a sample of 400 customers who have deposit savings product. The objective is to analyze the impact of age, account balance, and income on the amount of deposit savings. The independent variables are age, account balance, and income, while the dependent variable is the amount of deposit savings. Data analysis employs Multiple Linear Regression with Microsoft Excel software. Based on the analysis, it can be inferred: (1) Age, account balance, and income positively influence the amount of deposit savings; (2) The value is 34%, signifies the independent variables influences for 34% of the deposit savings amount, with the remaining 66% influenced by other independent variables